Ion Exchange and Corrosion Behaviour of Polyaniline Coated Mild Steel Electrode - Karci, Fati; Kabasakaloglu, Melike (Asian Journal of Chemistry, 2012)
The corrosion behaviour of mild steel and mild steel covered by the electrodeposited polyaniline films was investigated by electrochemical impedance spectroscopy. The electrodeposition of polyaniline coatings on mild steel was carried out by cyclic voltammetry using oxalic acid as the electrolyte. Protective properties of polyaniline coatings were investigated by monitoring the open-circuit potential and by applying electrochemical impedance spectroscopy. Nyquist plots explained as assuming underfilm oxidation at high frequency region and ion exchange process between polyaniline and electrolyte interface performed by oxygen reduction at low frequency region. Polyaniline layer provides corrosion protection due to having high ion exchange polarization resistance between the film and the electrolyte solution.